The electrochemical behaviour of polycrystalline nickel electrodes in different carbonate-bicarbonate ion-containing solutions - Bohé, A. E. (1990)
The dissolution and passivation of polycrystalline nickel in carbonate-bicarbonate ion-containing solutions covering wide ranges of pH and electrolyte concentration were investigated by employing voltammetric, galvanostatic and potentiostatic transient techniques. Results obtained with a rotating disc electrode allow the competing reactions related to the active-passive transition to be distinguished through the influence of the potential sweep rate and the rotation speed on the electrochemical behaviour of the system at fixed concentrations of either carbonate or bicarbonate ion. The first oxidation level of nickel corresponds mainly to Ni(OH)2 formation, the chemical dissolution of the surface layer and the precipitation of NiCO3 and Ni(OH)2. The partial removal of the prepassive layer is predominantly assisted by both the bicarbonate ion concentration and the electrode rotation. In the presence of chloride ions the formation of soluble Ni(II) species and NiCo3 in the potential range of the first oxidation level appears to be enhanced. This effect can be interpreted by taking into account competitive adsorption processes at the base metal between Cl− and OH− ions.